Hydrogen-modified interaction between lattice dislocations and grain boundaries by atomistic modelling. (18th March 2020) - Li, Jiaqing; Lu, Cheng; Pei, Linqing; Zhang, Che; Wang, Rui
Abstract: Dislocation plasticity in the vicinity of grain boundaries (GBs) plays a critical role in H-induced intergranular failure. Their interaction mechanisms under H environment, however, remain largely unexplored. Here, the underlying interaction of a screw dislocation with [ 1 1 ¯ 0 ] symmetric tilt GBs was studied by using molecular dynamics simulation, with special concerns on the role of solute H in it. Our results show several interaction mechanisms including dislocation dissociation, transmission, nucleation and reflection, depending on different glide planes and GB structures. The presence of H tends to transform these reactions into ones involving dislocation absorption due to H-hindered GB migration and H-enhanced localised plasticity. Furthermore, it is quantified that solute H leads to an increase in energy barrier for dislocation-grain-boundary interaction. After dislocation absorption, the GB segregated with H atoms is activated to a more disordered atomic structure, which can be correlated to the crack nucleation and hence the ultimate fracture. These findings advance a mechanistic understanding on H-induced plasticity-mediated intergranular failure. Highlights: DGB reactions (nucleation, transmission, dissociation and reflection) are observed. The presence of H atoms generally increases the energy barrier for DGB interactions. Solute H transforms those reactions into ones involving dislocation absorption. Dislocation absorption causes local GB activation, which greatly aids decohesion.